Prevalence and Risk Factors of QTc Prolongation During Pregnancy - Luo, Chaodi; Duan, Zhenzhen; Jiang, Yi; Liu, Peng; Yan, Yang; Han, Dan (Frontiers in Cardiovascular Medicine, 2022)
Background: Prolonged QT intervals have been observed in pregnant women, which predisposes them to a higher risk of potentially lethal ventricular arrhythmias. Therefore, this study was designed to evaluate the prevalence of QTc prolongation in Chinese hospitalized parturient women with single and twin pregnancies, and to explore potential risk factors associated with QTc prolongation. Methods: This retrospective study included 1218 patients from a large Chinese population between January 2014 and October 2020. Data from parturient women with single and twin pregnancies without pre-pregnancy cardiac disease were collected. QTc was corrected by the Fridericia formula (QTc=QT/RR(1/3)), and QTc ≥ 460 ms for females was defined as prolonged QTc, QTc ≥ 500 ms was defined as severely prolonged QTc. The prevalence and common risk factors of QTc prolongation during pregnancy were analyzed in this cohort. Uni- and multivariable logistic regression analysis were performed to identify clinical parameters associated with QTc prolongation in this population. Results: The prevalence of QTc prolongation was 48.19% among this population, 10.56% in single pregnancy, 89.44% in twin pregnancies. The prevalence of severely prolonged QTc was 23.48% among the total cohort, 0.49% in single pregnancy, and 46.47% in twin pregnancies. The mean QTc interval was significantly longer in twin pregnancies than in single pregnancy (498.65±38.24 vs. 424.96±27.67ms, P < 0.001). Systolic blood pressure, diastolic blood pressure, total cholesterol, serum uric acid, gestational hypertension and twin pregnancies were associated with QTc prolongation in parturient women. Conclusion: This is the first study to assess the prevalence and risk factors of QTc prolongation between single and twin pregnancies. QTc prolongation is more prevalent, and QTc intervals are significantly longer in twin pregnancies as compared to single pregnancy.